Comprehensive Intra-Institution stepping validation of knowledge-based models for automatic plan optimization. (January 2019) - Castriconi, R.; Fiorino, C.; Broggi, S.; Cozzarini, C.; Di Muzio, N.; Calandrino, R.; Cattaneo, G.M.
Highlights: KB-model for irradiation of nodes + prostate + vesicles in post-prostatectomy patients. The step-validation increased the confidence in using KB-optimization. Automatic KB-model showed better/equal performances compared to clinical plans. The interaction of a planner further improved planning performances. A gEUD reduction (up to 9 Gy) was seen in both KB optimization modalities. Abstract: Purpose: To develop and apply a stepping approach for the validation of Knowledge-based (KB) models for planning optimization: the method was applied to the case of concomitant irradiation of pelvic nodes and prostate + seminal−vesicles bed irradiation in post-prostatectomy patients. Methods: The clinical VMAT plans of 52 patients optimized by two reference planners were selected to generate a KB-model (RapidPlan, v.13.5 Varian). A stepping-validation approach was followed by comparing KB-generated plans (with and without planner-interaction, RP and only-RP respectively) against delivered clinical plans ( RA ). The validation followed three steps, gradually extending its generalization: 20 patients used to develop the model (closed-loop); 20 new patients, same planners (open-loop); 20 new patients, different planners (wide-loop). All plans were compared, in terms of relevant dose-volume parameters and generalized equivalent uniform dose ( gEUD ). Results: KB-plans were generally better than or equivalent to clinical plans. For RPvsRA, PTVs coverage was comparable, for OARs RP was always better. Comparing only-RPvsRA, PTVs coverage was always better; bowel\bladder V50Gy and D1%, bowel\bladder\rectum Dmean, femoral heads V40Gy and penile bulb V50Gy were significantly improved. For RPvsRA gEUD reduction >1 Gy was seen in 80% of plans for rectum, bladder and bowel; for only-RPvsRA, this was found in 50% for rectum/bladder and in 70% for bowel. Conclusion: An extensive stepping validation approach of KB-model for planning optimization showed better or equal performances of automatically generated KB-plan compared to clinical plans. The interaction of a planner further improved planning performances.